Epidemiologic study of human parvovirus B19 infection in East China. Issue 7 (6th January 2016) - Zhang, Lahong; Cai, Chengsong; Pan, Feng; Hong, Liquan; Luo, Xian; Hu, Sha; Xu, Jiali; Chen, Zhaojun
Abstract : Human parvovirus B19 (B19V) infection causes a number of diseases in humans, and, in some circumstances, can be life threatening. To understand the epidemiology of B19V infection in the greater metropolitan area of Hangzhou, East China, we performed surveys of IgM and IgG antibodies against B19V and quantification of B19V DNA, by using enzyme‐linked immunosorbent assay and quantitative PCR, respectively, in plasma samples from diverse groups. These groups included anemia patients, Mycoplasma pneumonia ‐ and Treponema pallidum ‐infected patients, HIV‐positive individuals, and healthy blood donor volunteers. Our results demonstrated a low level of B19V IgG antibody presence, ranging from 21.9% to 41.8% in all the groups tested, suggesting a low prevalence of B19V infection in the area. Of note, we found that two healthy blood donors and one Mycoplasma pneumonia ‐infected patient had B19V IgM antibody among 1, 290 plasma samples tested. The Mycoplasma pneumonia ‐infected patient had viremia with viral genome copies of 2.86 × 10 6 per ml of plasma. We detected a high rate of B19V DNA (7.1%) in HIV‐positive injection drug users. Importantly, an amino acid mutation of P558S in the large non‐structural protein NS1 was identified to be conserved among 14 B19V isolates from the HIV‐positive group but not in the B19V isolate of the Mycoplasma pneumonia ‐infected patient, representing a hallmark of B19V isolates that circulate in HIV1‐positive patients in the greater metropolitan area of Hangzhou, East China. J. Med. Virol. 88:1113–1119, 2016 . © 2015 Wiley Periodicals, Inc.